Epidemiology and Outcomes of Mild-Moderate Immunosuppressed (MMI) Patients with Pneumonia. (4th October 2017) - Neumann, Deeter; Gandhi, Tejal; Flanders, Scott; Conlon, Anna; Malani, Anurag; Nagel, Jerod
Abstract: Background: The current ATS/IDSA pneumonia guidelines lacks a concise definition of immunosuppression, which causes significant heterogeneity in antibiotic use for patients with MMI. Furthermore, the impact of mild-moderate immune suppression on pneumonia severity, incidence of multi-drug resistant (MDR) pathogens, disease course and clinical outcomes has not been well described. Methods: This multicenter observational cohort study included non-ICU patients diagnosed with pneumonia within 48 hours of admission from 10 hospitals between November 2015 and November 2016. MMI patients were defined as asplenic; HIV with CD4 count ≥200; non-neutropenic leukemic or solid malignancy receiving treatment in the previous 30 days; kidney transplant >1 year ago without rejection; receiving ≥15 mg/day prednisone for ≥30 days, TNF-alpha inhibitor, azathioprine or methotrexate use. All cause 30-day mortality, pneumonia severity, hospital length of stay (LOS), pneumonia readmissions, MDR pathogen (resistant to levofloxacin or ceftriaxone), and time to clinical stability were compared between MMI and immunocompetent patients. Results: A total of 2, 505 patients with pneumonia were included and 274 (11%) were classified as MMI. Similar rates of respiratory and blood cultures were obtained between MMI and immunocompetent groups (88.7% vs. 85.1%, P > 0.05), but the MMI group demonstrated a higher rate of culture positivity (19% vs. 15.5%, P = 0.013). There was no difference in culture positivity with traditional CAP pathogens between groups (5.5% vs. 5.2%, P > 0.05), but MMI patients had higher incidence of MDR pathogens (72.4% vs. 39.5%, P = 0.002). MMI patients presented with more severe disease (PSI of 115.6 vs. 87.2, P < 0.001), had higher mortality rates (7.7% vs. 2.1%, P < 0.001), and longer LOS (5.4 vs. 4.7 days, P < 0.001). However, time to clinical stability (2.6 vs. 2.64 days, P = 0.79) and recurrent pneumonia rates (34.8 vs. 33.8%, P = 0.89) were similar. Conclusion: MMI patients with pneumonia have a higher incidence of MDR pathogens. and culture positivity. MMI patients also have a higher mortality rate and longer LOS. Antibiotic regimens which extend coverage beyond traditional CAP pathogens may be needed in MMI patients, but broader coverage could be more targeted if risk factors for MDR pathogens in this population were identified. Disclosures: J. Nagel, Merck: Grant Investigator, Research grant